A PHYTOCHEMICAL STUDY OF KENCUR (Kaempferia galanga L) ETHANOL EXTRACT AS ANTI-BACTERIAL, ANTI-INFLAMMATORY, ANTI-OXIDANT, AND ANTI-FUNGAL - tobing, yauwan Tobing Lukiyono; Adriansyah, Agus Aan; Setianto, Budhi; Munawwaroh, Ahsantul; Ilmia, Fadhilatul; Wulansari, Febrianti; Rahmania, Almanda Putri (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2023)
Kaempferia galanga L or kencur is widely used as a raw material for traditional medicine (herbal medicine), phytopharmaceuticals, the cosmetics industry, spices, as well as a mixture of sauces, cigarettes in the kretek cigarette industry. Kencur or Kaempferia galanga L has anti-inflammatory activity which has been tested in acute inflammation (Kumar, 2020)The writing of this article is based on a study of literature obtained online in the form of articles, journals and other research results. The purpose of writing this article was to determine the effectiveness of the ethanolic extract of Kaempferia galanga L using the diffusion method in order to show significant inhibition on the growth of various types of microbes at a concentration of 10 L / disc as antibacterial, anti-inflammatory, antioxidant and anti-herbal. The conclusion obtained is that kencur (Kaempferia galanga L) has many benefits ethnobotanically from kempferia galanga L, but regarding its bioactivity it proves the activity of Kampferia galanga L as antifungal, anti-oxidant, anti-inflammatory and anti-bacterial.